2013
DOI: 10.1001/jamaophthalmol.2013.577
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of International Classification of Diseases, Ninth Revision, Clinical Modification Billing Codes for Common Ophthalmic Conditions

Abstract: To the EditorAn increasing number of analyses use administrative claims data to study the epidemiology, risk factors, and resource consumption associated with patients with ocular diseases. These sources of voluminous data allow researchers to study common and uncommon conditions and assess care delivered by different providers in various communities. Since claims data are collected primarily for billing, not research purposes, a concern is whether the diagnoses listed in the billing records reflect the actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 4 publications
1
56
1
Order By: Relevance
“…First, as with all claims data analyses, there is the potential that persons were miscoded or misdiagnosed with the conditions of interest. However, a recent study comparing the accuracy of billing codes to those obtained from actual medical records showed that billing records accurately reflected selected ocular conditions listed in the medical charts approximately 97% of the time (Muir, Gupta, Gill, & Stein, 2013). Second, as our population consisted of individuals with health insurance who had received some form of eye care, the results may not be generalizable to other populations who lack health insurance or those who have never received eye care.…”
Section: Discussionmentioning
confidence: 90%
“…First, as with all claims data analyses, there is the potential that persons were miscoded or misdiagnosed with the conditions of interest. However, a recent study comparing the accuracy of billing codes to those obtained from actual medical records showed that billing records accurately reflected selected ocular conditions listed in the medical charts approximately 97% of the time (Muir, Gupta, Gill, & Stein, 2013). Second, as our population consisted of individuals with health insurance who had received some form of eye care, the results may not be generalizable to other populations who lack health insurance or those who have never received eye care.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, billing code errors may also contribute to misclassification errors in determining presence and type of DR, though a recent study validating billing codes in common ophthalmic disorders (including proliferative DR) found a 97% accuracy rate compared to medical record documentation. 43 Clinical data such as visual acuity, retinal examination findings, or ophthalmologic imaging and testing were unavailable, and verification of DR presence or severity was infeasible. Youth were likely seen by eye care providers who had varying levels of experience and expertise in diagnosing DR and some may have had access to diagnostic equipment to facilitate diagnosis of DR while others may not have had access to such equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work comparing billing records with medical records found that billing records accurately capture persons with cataracts. 8 …”
Section: Methodsmentioning
confidence: 99%